Implementation of Slow Stroke Back Massage Therapy with Lavender Oil in Patients with Cervical Cancer Pain - Sartiningsih, Reni; Maryati, Siti (Global Health Science Group, 2024)
Cervical cancer is a malignant tumor that grows in the cervix caused by infection with the HPV virus. The nursing problem felt by cervical cancer patients is pain. Pain can be reduced by pharmacological management with analgesics and non-pharmacological management with SSBM with Lavender Oil. SSBM with lavender oil can reduce pain, is easy to do, doesn't require a lot of money, and can be done anywhere. Medical records of Dr. RSUP. Sardjito in 2023, there will be 22 patients with cervical cancer. Objective to find out the difference in pain scale before and after implementing SSBM with Lavender Oil in Cervical Cancer Pain Patients in the Bougainvillea Room 1, RSUP Dr. Sardjito Yogyakarta. Method: The research used was descriptive with a case study approach. Conducted on 1 respondent who experienced stage III B cervical cancer with mild - moderate pain scale with the implementation of SSBM with lavender oil for 30 minutes a day once for 3 consecutive days. Research on the application of SSBM with lavender oil showed a decrease in the pain scale in cancer patients cervix. The first to the third day in the hospital, the initial scale of 4 can decrease to scale 2. SSBM with lavender oil is an effort to reduce the pain scale in cervical cancer patients.